What drives leapfrogging? empirical assessment of consumer determinants of leapfrogging. (23rd February 2017) - Herrmann, Andreas; Sprott, David; Schlager, Tobias
Abstract : As part of the new product development process, firms face the challenge that consumers engage in leapfrogging, which is described as replacing the current product (P0 ) with the next generation (P2 ), instead of its latest version (P1 ). Yet, an overarching examination of the consumer determinants to leapfrogging is missing. This article closes the gap by conducting a field study in the automotive market. Results demonstrate that the tendency to leapfrog is mainly determined by the expected costs involved in switching from the old vehicle (P0 ) to the new vehicle (P1 ). The large effect of switching costs suggests that marketing practitioners should consider the price for the new product (P1 ) and the future product (P2 ), as well as the price for the old product (P0 ) to align their strategy concerning the lifecycle of their products. Not only does the article close an important gap in the current leapfrogging literature, it also emphasises a broader perspective of the competition such that a product not only competes with the products of other providers, but with its expected future generations.